About the vertical structure of currents in the intermediate Rio de la Plata: observational study - Dragani, Walter C. (2002)
The Río de la Plata is one of the most important estuarine systems of the world and the most developed basin of eastern South America. Water levels and currents have been measured at many locations of the river and a number of depth-integrated (2-D) models have been applied to determine its circulation. Nevertheless, the three-dimensional characteristics of the currents have been never analyzed neither by means of direct observations nor by means of 3-D models. In this work current data measured using an Acoustic Doppler Current Profiler are presented to show the vertical structure of currents in the intermediate Rio de la Plata. In February 2-3 2000, a transect of approximately 16 Km long was repeated eleven times during 25 hours obtaining 1972 current profiles. After applying a specific processing, sinusoids with M2 (12.42 hours) period was fitted to the data series using least squares fitting method. The M2 amplitudes and phases of the EW and NS components of the current and both components corresponding to the mean flow (residuals) were obtained along the transversal section of the transect. Results showed that currents present strong vertical gradients not only in the phases of the semidiurnal constituent but also in the mean flux in the intermediate zone of the Rio de la Plata. Although the intermediate Rio de la Plata is a very shallow basin results reveal that the current from upper to bottom layers can rotate more than 90°. These results indicate that currents respond strongly to the local winds but their effects are mainly manifested at the upper layer. Finally, results indicate that 3-D baroclinic models (including temperature and salinity fields and a realistic atmospheric forcing) should be used in order to obtain a reliable and complete representation of currents especially at the intermediate and outer zone of the Rio de la Plata.